Visual morbidity in thyroid eye disease in Asian Indian patients - Gupta, Roshmi (Indian J Ophthalmol, 2020)
PURPOSE: To describe visual morbidity in thyroid orbitopathy in Asian Indians and the factors influencing its onset. METHODS: A retrospective chart review was performed for patients with thyroid related orbitopathy seen between May 2014 and April 2019. Three hundred and one patients were included in the study. Relevant history, clinical findings, investigations, and treatment were documented. RESULTS: Nineteen percent of patients had at least 1 visual morbidity feature such as compressive optic neuropathy, exposure keratopathy or diplopia, requiring intravenous glucocorticoid. Male gender, older age, and diabetes were the significant risk factors for high visual morbidity (all P < 0.05). Systemic thyroid status, degree of proptosis, and duration of disease were not significant. Average dose of intravenous glucocorticoid needed was 3.8 g; 24 (7.9%) patients required orbital decompression, and 13 (4.3%) needed eyelid surgery. At the last follow-up, 97% of patients had vision 6/12 or better in both eyes. CONCLUSION: There is significant visual morbidity found in Indian patients with TED, even with moderate proptosis and systemic control of thyroid status. This is the first set of data on the subject.